CRIMINOLOGICAL ANALYSIS OF STUDENTS INVOLVED IN ONLINE SLOT GAMBLING (Case Study of X University Pekanbaru) - Kevin Alvario Fawwaz; Abdul Munir (Sisi Lain Realita, 2024)
The rapid development of the Internet today is not surprising. Because the development of the internet is directly proportional to the development of the gambling business via the Internet (online gambling). This started from researchers' observations among the student community. The act of online gambling is classified as a criminal offense (cyber crime). The aim of this research is: Researchers analyze using relevant theories, namely Reinforcement Theory, Cognitive Theory, Prospect Theory of students involved in online slot gambling, case study at Pekanbaru University. The research method that the author carried out is descriptive research. Descriptive research aims to ensure that the main problem is described, presented and explained further in such a way that the data and research results are easy to understand and rational. The results of the researcher's research are: The pattern of reinforcement inherent in the gambling system explained by Reinforcement Theory plays an important role. Additionally, Cognitive Behavioral Theory highlights how faulty thought patterns and inadequate emotional regulation contribute to this behavior. Then Prospect Theory tends to misjudge risks and opportunities in the context of gambling. This research shows that student involvement in online slot gambling is influenced by various psychological, social and economic factors. Theoretical approaches such as reinforcement theory, cognitive theory, and prospect theory provide a strong basis for understanding this phenomenon. To overcome this problem effectively, cooperation between educational institutions, government, families and society is needed. Education, strict regulations, psychological support, and social guidance can create an environment that empowers students to develop healthier and more responsible lifestyles. To address this problem effectively, a comprehensive strategy is essential.